2010
DOI: 10.1016/j.cub.2009.10.078
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Export from Mammalian Cell Nuclei Is Dependent on GANP

Abstract: SummaryBulk nuclear export of messenger ribonucleoproteins (mRNPs) through nuclear pore complexes (NPCs) is mediated by NXF1. It binds mRNPs through adaptor proteins such as ALY [1, 2] and SR splicing factors [3] and mediates translocation through the central NPC transport channel via transient interactions with FG nucleoporins [4–10]. Here, we show that mammalian cells require GANP (germinal center-associated nuclear protein) for efficient mRNP nuclear export and for efficient recruitment of NXF1 to NPCs. Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
144
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(155 citation statements)
references
References 36 publications
(33 reference statements)
10
144
1
Order By: Relevance
“…In agreement with a former study showing that GANP interacts with the mRNA export receptor NXF1 (Wickramasinghe et al, 2010), we could show that NXF1 colocalizes with EGFP-ENY2 and EGFP-PCID2 at the nuclear periphery ( Fig. 2A; supplementary material Fig.…”
Section: Journal Of Cell Sciencesupporting
confidence: 80%
See 1 more Smart Citation
“…In agreement with a former study showing that GANP interacts with the mRNA export receptor NXF1 (Wickramasinghe et al, 2010), we could show that NXF1 colocalizes with EGFP-ENY2 and EGFP-PCID2 at the nuclear periphery ( Fig. 2A; supplementary material Fig.…”
Section: Journal Of Cell Sciencesupporting
confidence: 80%
“…In human, depletion of most TREX-2 subunits results in mRNA nuclear accumulation. Some subunits such as GANP, ENY2 and CETN2 were shown to associate with the nuclear envelope where GANP is required for ENY2 localization (Wickramasinghe et al, 2010;Jani et al, 2012). Conversely, ENY2 depletion did not affect GANP localization.…”
Section: Introductionmentioning
confidence: 99%
“…GANP is involved in mRNA export in mammalian cells (30) and particularly in the selective export of Shugoshin-1 mRNA required for cell cycle progression through the M phase (20). The lack of GANP results in embryonic lethality at embryonic day 12.5 in mice and induces homology-mediated DNA hyperrecombination in cells, similar to that observed in suppressor of actin 3-deficient yeast cells (31,32).…”
Section: Discussionmentioning
confidence: 82%
“…region of GANP is homologous to the Saccharomyces cerevisiae SAC3 protein, a component of the SAC3/THO complex involved in RNA export following transcription in yeast, and therefore GANP is proposed as a component of the mammalian transcription/ export-2 complex (31,32). Recently, we demonstrated that GANP interacts with cytoplasmic AID and assists its nuclear localization to augment its transport to the transcribed IgV region segment in B cells (33).…”
mentioning
confidence: 99%